(untitled) (The International Research Journal of Management Science, 2021)
The study aimed to examine the influence of management accounting practices on organizational performance with the mediating effect of rationalizing managerial decisions of the Nepalese listed manufacturing companies. It is based on survey data from 221 respondents from the seven listed manufacturing companies, whose shares are traded regularly in Nepal’s secondary market. The data were analyzed using confirmatory factor analysis, path analysis, and structural equation modeling to dissect and decipher details. The study’s findings indicated that management accounting practices had no significant impact on organizational performance, and there was no mediating role of rationalized managerial decisions. However, rationalized managerial decisions themselves had a positive and significant impact on organizational performance. The study was limited to capturing only Nepal’s listed manufacturing companies and applied one survey technique method with a few standard questionnaires to collect data. Different sectors and higher sample sizes may be considered to improve the generalizability of the analysis. The authors hoped that it contributes to the existing literature in management accounting and organizational performance. It may attract the concerned personnel’s attention towards the management accounting practices to make effective managerial decisions and better organizational efficiency.